ER stress mediated regulation of miR23a confer Hela cells better adaptability to utilize glycolytic pathway. Issue 6 (7th March 2018) - Poyyakkara, Aswini; Raji, Grace R.; Kunhiraman, Haritha; Edatt, Lincy; Kumar, Sameer V.B.
Abstract: Cancer cells exhibit increased dependency on aerobic glycolysis, a phenomenon referred as the "Warburg effect" and therefore, blocking glycolysis by using non‐metabolizable analogues of glucose, like 2‐Deoxy glucose (2‐DG), has been proposed to be of huge therapeutic importance. One of the major drawbacks of using 2‐DG as a chemotherapeutic agent is that it can induce ER stress. ER stress is a hall mark in many solid tumors and the unfolded protein response (UPR) associated with it initiates many survival mechanisms in cancer cells. In the present study, we report a novel survival mechanism associated with ER stress, by which the cancer cells become more adapted to aerobic glycolysis. When ER stress was induced in Hela cells by treating them with 2‐DG or Thapsigargin (TG) the expression and activity of LDH was significantly up regulated, conferring the cells a greater glycolytic potential. A simultaneous decrease was observed in the expression of miR‐23a, which was predicted in silico to have target site on the 3′UTR of LDH A and B mRNAs. miRNA over expression studies and mRNA degradation assays suggest that miR‐23a could target LDH A and LDH B mRNAs. Further on the basis of our results and previous scientific reports, we propose that "c‐Myc, " which is over expressed during ER stress, repress the expression of miR‐23a, which in turn regulates the expression of its target genes viz., LDH A and LDH B, thereby making the cells more competent to survive in tumor microenvironment, which requires efficient use of aerobic glycolysis. Abstract : ER stress in tumor cells can render them more adaptive towards tumor metabolism by upregulating LDH A and LDH B genes in a miR23a dependent mechanism, thereby switching on to more efficient glycolytic pathway.